Kinship System Border as Social Capital Community - gregorius henu basworo (The Republic of Indonesia Defense University, 2017)
This research on kinship systems of border communities as social capital in overcoming the threat of non-military in District Paloh Sambas district of West Kalimantan Province. In analyzing the problem of research used Kinship Systems theory, the theory of social interaction and social capital theory, the concept of border area and the concept of non-military threats. This study uses a qualitative method. Data collected through observation, interview, and literature study. The results showed that the alliance system in the village of Temajuk not only is biological (blood ties or marriage), but also sociological (local socio-cultural influences). This kinship system produces social interaction is associative because it was built on the basis of trust (trust) among them. Trust is the basis of social capital. The strong social capital the communities in Temajuk can overcome the threat of non-military in the border region. The findings show that social capital is an important aspect of national defense